Passageway business regulation and bank loan financing: A quasi-natural experiment based on new asset management rules - Siyi He; Qinglu Jin (China Journal of Accounting Studies (CJAS), 2024)
Using the exogenous shock of New Asset Management Rules (NAMRs), this paper examines the impact of strengthening passageway business regulation on bank loan financing. We find that since the introduction of the NAMRs, firms that used to adopt passageway financing are obtaining more bank loans. When firms change their business to directions supported by industrial policies, they are more likely to obtain loans from state-owned commercial banks. In addition, firms can improve their performance to obtain loans from other commercial banks. Further tests show that after firms turn to loan financing, the cost of loans can decrease but other financing behaviours do not change significantly. The test of economic consequences also shows that after considering adjustment costs, turning to bank loan financing does not lead to worse net income. This paper provides new insights for understanding the micro effects of shadow banking regulation and improving China's financial regulatory policies.
Keywords: 650; bank loan; financial risk; Passageway business; shadow banking